Application of Advanced Virtual Reality and 3D Computer Assisted Technologies in Computer Assisted Surgery and Tele-3D-Computer Assisted Surgery in Rhinology - Klapan, Ivica; Raos, Pero; Galeta, Tomislav; Šimičić, Ljubimko; Lukinović, Juraj; Vranješ, Željko; Maleš, Josip; Belina, Stanko; Ćuk, Višeslav (IntechOpen, 2011)
None